Pengembangan media kartu karier untuk meningkatkan pengambilan keputusan karier siswa - Andini, Aulia Prima; Ilahi, Fauzi Nur; Almuin, Nani (Orien: Cakrawala Ilmiah Mahasiswa, 2024)
the method used in this research uses the Research and Development (RnD) development method based on the theory of Borg and Gall (1983). The research produced a product in the form of a career card through three stages of assessment and revision which resulted in a Media Expert of 87.50%, a BK Material Expert of 92.19%, and a Language Expert of 90% with a score category of "Very Appropriate" being tested. The aim of this research is to determine the process of developing career card media in improving career decision making for class XII students at SMA Al-Itqan Depok. The sample used in the research was 5 students from class XII. Data analysis used used a Likert Scale with an increasing score of 2.75% with a score category of "Good" because the average score was 64.00%. The conclusion in this research is that the career card is worth testing and has increased career decision making among class XII students at SMA Al-Itqan Depok.